ANALYSIS THE EFFECT OF SERVICE QUALITY and PRODUCT QUALITY to CUSTOMER SATISFACTION at XO MEN'S WEAR PONTIANAK - B31111093, Wanfirto (Jurnal Manajemen Update, 2016)
The research was done at XO Men's Wears in Pontianak. In this study aims to determine the influence of Quality Service and Quality Products to Customer Satisfaction, Where is the independent variable that consists of a variable Quality Service and Quality Products variable on the dependent variable Customer Satisfaction. The research sample is 100 respondents. The sampling technique used purposive sampling, the sampling is with specified criteria. The customers was at least 17 years old, residents of the Pontianak city and ever make a purchase. The analysis was performed by using multiple linear regression. The results of analysis first hypothesis is accepted with the t-tes is 2.372 greater than t table. Thus, the Service Quality positive and significant impact on customer satisfaction. In the second hypothesis was also accepted with the t-test value is 3.731 greater than t table. Thus, product quality significant and positive impact on customer satisfaction. The results of the analysis of the coefficient of determination (R) is 66.70% with variable customer satisfaction can be explained by the variation of the variable Service Quality and Product Quality variable, while 33.30% is explained by other variables that not included in this research.       Keywords: Quality Service, Quality Products, Customer Satisfaction